PROFITABILITY DAN PRAKTIK TAX AVOIDANCE DI INDONESIA - Nursoleh, Muhammad Rizki; Tjun Tjun, Lauw (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2025)
The main focus of this study is to investigate how profitable tax avoidance is for non-financial companies in Indonesia, with operating cash flow acting as a control variable. Using previously published data and quantitative methodology, referring to annual reports published by 40 companies for the period 2019-2024 that have been submitted to the Indonesian Stock Exchange (IDX). The analysis process uses a multiple linear regression model run through the SPSS application version 29. The findings indicates that profitability has no significant impact on tax avoidance. Likewise, cash flow from operating activities shows no significant influence on tax avoidance. The regression model accounts for only 0.5% of the variance in tax avoidance, suggesting that other factors outside the scope of this study may play a more substantial role in explaining corporate tax avoidance behavior. The limited explanatory power of the model underlines the necessity of exploring additional variables in future studies. The scope of this study only includes only two financial indicators and a specific observation period. Therefore, the results should be interpreted carefully, taking into account the study’s context and scope. Keywords: Tax Avoidancce, Return on Assets, Cash Effective Tax Rate, and Operating Cash Flow